The Bravest Dog - Ayinde, Bukola (Nigeria, 2022)
Bisi has a dog, Teeny, who is different from the other dogs. Teeny has only two legs so he cannot play or rollover like the other dogs. The children in the neighbourhood also make fun of him because he is different.
Keywords: Animal; Juvenile Fiction